Tourism destination competitiveness with a particular focus on sport: the current state and a glance into the future – a systematic literature analysis. Issue 1 (2nd January 2021) - Happ, Elisabeth
ABSTRACT: This literature review focuses on tourism destination competitiveness in the field of sport (TDC sport) or, more specifically, on mapping literature dealing with factors influencing and measuring TDC sport. Existing literature has mainly focused on factors influencing tourism destination competitiveness (TDC) and on measuring TDC in general, paying no attention to two factors: First, there is an emerging line of research and theory building that bridges the fields of leisure, sport, and tourism; and second, when tourism and sport are concerned, generic models in their original form may not be specific enough and some of their dimensions and elements may not be suitable. Thus, this systematic literature analysis (a) focused on TDC in the context of sport, taking into account that sport has unique characteristics, (b) reviewed the current state of empirical research by framing a conceptual model of factors influencing TDC in a sport context, and (c) revealed gaps for future research. Results showed that no single universal set of indicators is applicable to all destinations and issues at all times. Furthermore, approaches in the existing literature have suggested that sport contributes to the construction of a country's brand and provides a unique advantage. Moreover, the analysis highlighted sport-specific factors and addressed the debates about 'soft' factors and the notion of a destination as 'the' place to be.